"Cut out the middleman" – Automating Business Processes with Blockchains and Smart Contracts. Issue 39 (2022) - Jesse, Dr. Norbert
Abstract: Competence in data management is fundamental for the survival of companies. In this paper we go beyond topics like data integration, data quality, data governance or data wrangling. The notion is to outline the conceptual approaches of blockchain technology and smart contracts as an innovative approach to sharing data and automating contractual processes between interested parties. Cryptocurrencies - with bitcoin the first and most prominent one – have become highly relevant on the financial markets. The underlying technology for crypto money follows a distributed ledger concept called blockchain. However, blockchain technology today amounts to much more than storing virtual money, having gained new ground with the capability to implement so-called smart contracts, i.e., software code as part of the chain. In this discussion we outline the concept of distributed ledgers and blockchain and outline fundamentals of smart contracts. Finally, proof of concepts and first applications exemplify the options that companies now have to enhance their business.